INTERVENSI KELUARGA DALAM REKRUTMEN KELOMPOK BELAJAR SANGGAR PELITA - Elin Purnama; Fajar Utama Ritonga (Nindikayla Institute, 2023)
The practitioner's Field Work II Practicum got a client, namely a lamp studio or a children's study house, to seek knowledge. Practitioners assist clients in solving problems up to the stage of problem-solving using the Groupwork method, which consists of several stages: Assessment Stage, Planning Stage, Intervention Stage, and Evaluation Stage. The practitioner also accompanies clients in the recruitment process at the Pelita studio, starting from the family, community, and local youth so that they are willing to be involved in learning houses for children. Data collection techniques are carried out through interviews with clients, and in the Assessment stage, the Participatory Learning and Action (PLA) method is used to assist clients in finding the root of the problem. Practitioners will also assist and supervise the implementation of the program correctly